Research and imagination: creative prompts for the production of theses in social sciences and humanities (Praxis Educativa, 2022)
A thesis can be an act of imagination. But, in many cases, the imagination ends up retracted under the structures and forms to which we suppose academic production should submit. In this text I share some creative incitements to awaken the imagination in the thesis production process. For that, I recover reflections around the procedures of aesthetic creation. The proposal aims to create research more concerned with curiosity –personal, political, epistemic and/or social– than with disciplinary demands. The article is structured around four assumptions: a) apparitions or generative images emerge in the fieldwork, b) writing allows us to reflect on these images, c) if they are approached collaboratively, these reflections enrich the conceptualization process, and d ) the bad combinations –unexpected relationships between the field material– allow us to go deeper into the problem.
Keywords: Methodology; artistic creation; field work; ethnography; conceptualization